Asuhan kebidanan Pada Ny. "N" Pada Ibu 2 Jam Post Partum dengan Preeklamsia di RS Amelia Pare Kediri Tahun 2022 - Endah Luqmanasari; Jelita Yusriani Markus (Jurnal Vokasi Kesehatan, 2022)
The puerperium period or also known as the puerperium period is a period when the reproductive organs slowly undergo changes like the state before pregnancy (Maritalia, 2014). In the puerperium, it is quite important for health workers to always monitor, especially related to complications of pre-eclampsia and eclampsia. It is a disease caused by pregnancy. The purpose of this case study is to provide Obstetric care to Mrs." N" with preeclampsia of the Puerperium period. The research design used is a case study with research subjects in Ny. "N" . Data collection methods through interviews, observation and documentation studies. The results of midwifery care in Mrs." N" obtained data on the puerperium of the mother experiencing mild preeclampsia. The problem experienced by the mother is high blood pressure. Problem management has been given according to the diagnosis and advice of the doctor. Midwifery care can increase the effectiveness of health care in mothers as a whole so that it does not endanger the mother and increase patient satisfaction in obtaining midwifery services.